Toxascaris leonina in dogs – A nematode species of high prevalence in some regions of Eurasia - Bauer, Christian; Lider, Lyudmila A.; Ussenbayev, Altay E.; Seitkamzina, Dinara M.; Zhanabayev, Asylbek A.; Maksimov, Pavlo; Knaus, Martin; Justus Liebig University Giessen (My University, 2024)
A recent meta-analysis of studies from around the world had shown a global prevalence of Toxascaris leonina in stray dogs of about 7%. However, studies from Eurasian regions, where higher percentages of positive dogs were often found, were under-represented in this meta-analysis. This prompted the present study. Its main objective was to examine free-roaming dogs from the capital city of Kazakhstan to obtain information on the current occurrence of T. leonina egg shedding compared to Toxocara spp. Faecal samples from 500 free-roaming dogs from the city of Astana and its suburbs were collected 1–2 days after admission to the municipal animal shelter during three time periods (May to October 2019, September 2020, and April 2021). Samples were examined by a saline flotation method. Nematode egg-positive samples were subjected to a modified McMaster method to determine the number of eggs per gram of faeces (EPG). Toxascaris leonina eggs were found in 53.8% and Toxocara spp. eggs in 14.8% of the dogs examined. The prevalence of T. leonina egg shedding was significantly associated with age class but not with sex: dogs aged between 6 months and 2 years were more likely to be T. leonina egg positive than puppies. The intensity of T. leonina egg shedding was also age dependent: dogs aged between 6 months and 2 years had significantly higher EPGs compared to younger or older animals. In contrast, the prevalence of Toxocara spp. egg shedding was associated with both age class and sex: dogs older than 2 years were less likely to shed Toxocara spp. eggs than puppies, and females were less likely to be Toxocara spp. egg positive compared to males. The present results confirm those of other studies in Eurasian regions. It is therefore reasonable to assume that the global prevalence of T. leonina infection has been underestimated and should be revised accordingly.
Keywords: ddc:540